Developing Information System for Managing and Booking Rooms and Facilities in a Retreat House - Veronica S. Moertini; Vania Natali; Edo F. Haryanto; Dearen Hippy (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
One well-known retreat place in West Java is the Pratista Retreat House, which is located in Cisarua, West of Bandung. It is managed by monks from the Order of Sanctae Crucis. This retreat house complex is quite large and has more than 60 rooms which can accommodate more than 200 retreat participants. Retreat participants generally rent rooms in groups. This house also provides several facilities that can be rented. Based on the survey results, reservations for retreat houses and facilities are conducted via telephone or other communication media. This creates problems both for the public (it is difficult to find a free time slot) and the manager (it is difficult to get reports of room availability timely). A community service activity by a team from Parahyangan Catholic University was working to develop an information system consisting of two website modules, each used by the managers and the public. The core features of the website for managers are for managing assets, orders, and viewing various reports. Meanwhile, the features for the public include viewing room and facility information, placing orders, and managing orders. The system has been developed, launched, and utilized by the Pratista management and is available to the public. The website for the public is available at https://pratista.oscsangkristus.or.id/.